Sustentabilidad y desarrollo económico circular - Mora Barrero, Ivonne Cleopatra (2024)
The study's primary objective is to validate the evolution of management theory, focusing on the transition from a traditional shareholder value creation approach to a broader recognition of the social role of businesses. Additionally, it analyzes the introduction of the circular economy as a response to environmental challenges, promoting sustainable production and considering its role in economic growth and resource stability. An exploratory-analytical approach based on cluster analysis was used to identify and understand the interrelationships between the circular economy, Cradle to Cradle philosophy, and sustainability. Information was gathered from scientific databases such as Scopus® and Web of Science®, allowing for the analysis of a wide range of relevant publications. The cluster analysis revealed three main groupings: sustainability, circular economy, and economic development. These clusters showed how these concepts are interrelated and how they can be integrated into business strategies to effectively address global challenges. The resulting dendrogram facilitated the visualization of these interconnections and provided a clear hierarchical structure of the analyzed concepts. The circular economy is presented not only as an environmentally responsible strategy but also as an innovative paradigm that optimizes resources, drives sustainability, and promotes greater resilience in industrial systems.